2013
DOI: 10.1038/ejhg.2013.195
|View full text |Cite
|
Sign up to set email alerts
|

Variants at IRX4 as prostate cancer expression quantitative trait loci

Abstract: Genome-wide association studies (GWAS) have identified numerous prostate cancer-associated risk loci. Some variants at these loci may be regulatory and influence expression of nearby genes. Such loci are known as cis-expression quantitative trait loci (cis-eQTL). As cis-eQTLs are highly tissue-specific, we asked if GWAS-identified prostate cancer risk loci are cis-eQTLs in human prostate tumor tissues. We investigated 50 prostate cancer samples for their genotype at 59 prostate cancer riskassociated single-nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…rs10993994 was associated with NCOA4 in normal tissue with p=5.7x10 −5 , but was null in tumor (p=0.64), consistent with a previous finding (19). We also confirmed other previous findings (20, 21): rs12653946 with IRX4 (in tumor and normal), rs8102476 with PPP1R14A (in tumor and normal), rs6465657 with LMTK2 (in tumor only), and rs5945619 with NUDT10 (in tumor only). However, we did not confirm an association of rs4430796 with HNF1B in normal tissue (p=0.66) (19) or associations with FAM83F (p=0.29), YIF1B (p=0.37) , FAM98C (p=0.17) , FOXP4 (p=0.19) , or TFEB (p=0.78) in tumor tissue (21).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…rs10993994 was associated with NCOA4 in normal tissue with p=5.7x10 −5 , but was null in tumor (p=0.64), consistent with a previous finding (19). We also confirmed other previous findings (20, 21): rs12653946 with IRX4 (in tumor and normal), rs8102476 with PPP1R14A (in tumor and normal), rs6465657 with LMTK2 (in tumor only), and rs5945619 with NUDT10 (in tumor only). However, we did not confirm an association of rs4430796 with HNF1B in normal tissue (p=0.66) (19) or associations with FAM83F (p=0.29), YIF1B (p=0.37) , FAM98C (p=0.17) , FOXP4 (p=0.19) , or TFEB (p=0.78) in tumor tissue (21).…”
Section: Resultssupporting
confidence: 92%
“…In addition to confirming the MSMB and NCOA4 results, NUDT11 was associated with rs5945619 and SLC22A3 was borderline significantly associated with rs9364554 in both tumor and normal tissue; and HNF1B was associated with rs4430796 in normal tissue only (19). Harries et al observed an association between rs6465657 and expression of nearby LMTK2 (20), while Xu et al found a proxy for rs12653946 to be strongly associated with the expression of nearby IRX4 (21). …”
Section: Introductionmentioning
confidence: 99%
“…Over-expression of IRX4 significantly increased invasion relative to controls in all conditions examined and IRX4 had high relative expression in a subset of basal-like breast cancers (Figures 5,6). IRX4 is a homeobox transcription factor involved in cardiogenesis, marking a ventricular-specific progenitor cell (Nelson et al, 2016) and is also associated with prostate cancer risk (Xu et al, 2014). SNX29 belongs to the sorting nexin protein family that function in endosomal sorting and signalling (Marat and Haucke, 2016).…”
Section: Novel Twist and Snail Functional Targets Influence Invasion mentioning
confidence: 99%
“…Multiple studies have shown that PrCa-and other disease-associated variants are enriched near variants that correlate with gene expression levels [9][10][11][12][13] . In fact, recent approaches have integrated expression quantitative trait loci (eQTLs) with GWAS to implicate several plausible genes for PrCa risk (e.g., IRX4, MSMB, NCOA4, NUDT11 and SLC22A3) 5; [14][15][16][17][18][19][20][21] . While overlapping eQTLs and GWAS is powerful, the high prevalence of eQTLs 22 coupled with linkage disequilibrium (LD) renders it difficult to distinguish the true susceptibility gene from spurious co-localization at the same locus 23 .…”
Section: Introductionmentioning
confidence: 99%